2011
DOI: 10.18388/abp.2011_2235
|View full text |Cite
|
Sign up to set email alerts
|

Different statins produce highly divergent changes in gene expression profiles of human hepatoma cells: a pilot study.

Abstract: Statins are inhibitors of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR), the key enzyme of the sterol biosynthesis pathway. Statin therapy is commonly regarded as well tolerated. However, serious adverse effects have also been reported, especially during high-dose statin therapy. The aim of our study was to investigate the effect of statins on gene expression profiles in human hepatoma HepG2 cells using Affymetrix Human Genome U133 Plus 2.0 arrays. Expression of 102, 857 and 1091 genes was changed substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…Similar results were observed in human skeletal muscle-like cells [14] and human hepatoma HepG2 cells [15]. In those studies statins increased the expression of numerous cholesterol synthesis-related genes.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results were observed in human skeletal muscle-like cells [14] and human hepatoma HepG2 cells [15]. In those studies statins increased the expression of numerous cholesterol synthesis-related genes.…”
Section: Discussionsupporting
confidence: 80%
“…( Figure 2B and C). On mRNA level as assessed by qPCR, we found that statins increased HMGCS and HMGCR ( Figure 2D), the same effects that have been described for liver including LDL receptor 23 . Eight protein coding transcript variants are known for LDLR.…”
Section: Muscle Cells Possess a Similar Repertoire For Cholesterol Bisupporting
confidence: 82%
“…Their pharmacological actions and impact on gene expression have been shown to differ [43], [45], [46] and thus, depending on the cells to be treated, the most effective drug has to be determined. Here we show that in case of MPC and MTT, the lipophilic statins fluvastatin, simvastatin, and lovastatin considerably reduced cell proliferation, with simvastatin and fluvastatin showing slightly stronger effects.…”
Section: Discussionmentioning
confidence: 99%